2020
DOI: 10.1016/j.cegh.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition among elderly a multifactorial condition to flourish: Evidence from a cross-sectional study

Abstract: A B S T R A C TAim: The negative outcomes like an increased risk of falling, anemia, immune dysregulation, impaired cognitive status, reduced muscle function, increased morbidity and mortality associated with malnutrition are believed to affect the economy of the country in the future years. In this backdrop, this study aims to evaluate the nutritional status and different risk factors associated with malnutrition among elderly patients at a tertiary care public teaching hospital. Methods: This questionnaire-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Which estimated the number of elderly in Egypt reached 7.3 million in 2020. This result is nearly in agreement with Rashid et al (15) in India, which found that the average age of the studied elderly was 68.2 ± 0.4. Likewise, Arthur et al (16) in Ghana, found that the target population for the study was who were 60 years and above.…”
Section: Discussionsupporting
confidence: 93%
“…Which estimated the number of elderly in Egypt reached 7.3 million in 2020. This result is nearly in agreement with Rashid et al (15) in India, which found that the average age of the studied elderly was 68.2 ± 0.4. Likewise, Arthur et al (16) in Ghana, found that the target population for the study was who were 60 years and above.…”
Section: Discussionsupporting
confidence: 93%
“…Physiological functions declining with aging include body composition, brain function, gastrointestinal (GI) tract function, fluid balance, bones and joints, or cardiovascular system, among others . Sarcopenia, loss of muscle mass associated with a protein deficit, asthenia, depression, or weakness of the immune system often occur in elderly. , The masticatory deficiency in elderly, i.e., leading to food boluses with larger particle size distribution and more difficult to swallow, has been reported to influence the nutrients digestibility . Also, a decline in the GI tract function has been reported to be partially responsible for the protein deficit.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of literature has shown that low-quality diets contribute to excessive weight gain [ 1 ], obesity [ 2 ], and major NCDs that include type 2 diabetes [ 3 , 4 ], cardiovascular diseases [ 5 , 6 ], nonalcoholic fatty liver disease [ 4 ], and several cancers [ 7 ]. Diets lacking essential vitamins and nutrients can also lead to health conditions related to malnutrition, a growing problem among the elderly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%